The value of self-stated attribute importance to overall satisfaction - Taplin, Ross (Pergamon, 2012)
This paper provides insights into techniques used to determine the attributes that influence overall satisfaction. A survey of zoo visitors illustrates several key findings relevant for both managers interpreting survey results and researchers designing studies. First, the assumption of importance - performance analysis (IPA) that self stated importance measures the influence of attribute performance on overall satisfaction is endorsed. Second, relative importance is shown to be vital as it improves the prediction on overall satisfaction from attribute performance while absolute importance makes it worse. Third, techniques using self-stated relative importance are shown to be superior to statistical techniques such as regression, however new techniques using both self-stated importance and regression are shown to be even better. These findings apply generally to tangible products in marketing and management as well as to tourism services.